2021
DOI: 10.3389/fnins.2021.525615
|View full text |Cite
|
Sign up to set email alerts
|

Icaritin Alleviates Glutamate-Induced Neuronal Damage by Inactivating GluN2B-Containing NMDARs Through the ERK/DAPK1 Pathway

Abstract: Excitatory toxicity due to excessive glutamate release is considered the core pathophysiological mechanism of cerebral ischemia. It is primarily mediated by N-methyl-D-aspartate receptors (NMDARs) on neuronal membranes. Our previous studies have found that icaritin (ICT) exhibits neuroprotective effects against cerebral ischemia in rats, but the underlying mechanism is unclear. This study aims to investigate the protective effect of ICT on glutamate-induced neuronal injury and uncover its possible molecular me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…In this research, DOX enhanced the gene expression of P38MAPK and ERK1. These results coincide with those of Liu et al [ 86 , 87 ]. On the other hand, nanoceria co-treatment significantly downregulated the gene expression of the two kinases, in line with another study [ 88 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this research, DOX enhanced the gene expression of P38MAPK and ERK1. These results coincide with those of Liu et al [ 86 , 87 ]. On the other hand, nanoceria co-treatment significantly downregulated the gene expression of the two kinases, in line with another study [ 88 ].…”
Section: Discussionsupporting
confidence: 93%
“…The ERK pathway is essential for neuronal survival ( 69 ) and is required for the synthesis of Arc, a protein that plays a crucial part in long-term memory formation, neuronal activity and synaptic plasticity ( 41 ). A recent study found an increase in Arc staining after doxorubicin treatment, suggesting that doxorubicin induces neuronal activity.…”
Section: Direct Neurotoxicitymentioning
confidence: 99%
“…Next, we examined the possible roles of several signaling pathways implicated in the ATP-mediated protective response to glutamate-induced neuroexcitotoxicity, such as PI3K/Akt and Erk1/2 signaling pathways ( Ali et al, 2018 ; Chen et al, 2020 ; Liu et al, 2021 ). We monitored the protein levels of phosphorylated Erk1/2 (p-Erk1/2) and phosphorylated Akt (p-Akt), and found that the levels of p-Erk1/2 were down-regulated by glutamate in SH-SY5Y cells; whereas the treatments of extracellular ATP significantly increased the expression of p-Erk1/2 ( Figure 4A ), suggesting that ATP activates Erk1/2 to antagonize glutamate.…”
Section: Resultsmentioning
confidence: 99%